2014
DOI: 10.1353/hpu.2014.0171
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Medicaid Funding of Smoking Cessation Treatment Programs: An Application to State-Level Health Care Savings

Abstract: Findings suggest that making tobacco-dependence treatment freely available to low-income smokers can produce net savings for state governments within a short period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Finally, the present study assumed relatively high relapse rates, whereas these other studies assumed either no relapse, 27 or lower relapse rates. 28 The present study's sensitivity analysis using lower relapse rates showed larger cessation-induced healthcare savings.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Finally, the present study assumed relatively high relapse rates, whereas these other studies assumed either no relapse, 27 or lower relapse rates. 28 The present study's sensitivity analysis using lower relapse rates showed larger cessation-induced healthcare savings.…”
Section: Discussionmentioning
confidence: 65%
“…Richard and colleagues 27 found that comprehensive coverage for pharmacotherapy and counseling for Massachusetts Medicaid beneficiaries yielded a net savings with a benefit−cost ratio of 3.12 in 2.5 years. McCallum et al 28 found that covering counseling and nicotine replacement therapy for Alabama Medicaid beneficiaries achieved a net savings with a benefit−cost ratio of 1.95 within 2 years. This study showed that the UC+NP+FI versus UC treatment would yield positive savings, though the savings would not occur as quickly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to better physical health outcomes, successful tobacco treatment (TT) can also improve mental health functioning . Moreover, TT decreases rehospitalizations and reduces the likelihood of leaving against medical advice . However, state‐operated/supported psychiatric facilities fall short of providing TT for patients .…”
Section: Introductionmentioning
confidence: 99%